2015
DOI: 10.5430/jnep.v5n8p109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the planned therapeutic communication program on therapeutic communication skills of pediatric nurses

Abstract: Background: Therapeutic communication is the basis of interactive relationships among health team and their patients: that affords opportunities to establish rapport, understand the client's experience, formulate individualized or client interventions and optimize health care resources. Aim: this study was carried out to assess the effect of a planned therapeutic communication program on therapeutic communication skills of pediatric nurses. Methods: Setting: the study was carried out at Shebin El kom and Benha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
1
10
0
2
Order By: Relevance
“…Therapeutic communication is a central element of the nurse-patient interaction, which helps to achieve positive health outcomes (Lima et al., 2012; Rezende et al., 2013). Younis et al. (2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic communication is a central element of the nurse-patient interaction, which helps to achieve positive health outcomes (Lima et al., 2012; Rezende et al., 2013). Younis et al. (2015).…”
Section: Introductionmentioning
confidence: 99%
“…The nursing process is achieved through an interpersonal environment. Each interaction relied on the principle that promotes well-being and enhances satisfaction (Younis et al., 2015; Henson, 2007). According to the World Health Organization (WHO) report, communication serves an instrumental role that is at the heart of who we are as human beings (WHO, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic interaction between the child, family, and nurse can lead to the independence of caregivers, lower workload, higher care satisfaction, and possibly lower side effects and shorter hospital stay [3]. Many studies consider the ability to communicate properly as one of the key characteristics of a nurse [10]. Shimoinaba et al reported that nurses, who communicated correctly and completely during patient care over a longer period and in a more appropriate environment, were able to prepare patients and their caregivers to express their feelings and have better communication [11].…”
Section: Introductionmentioning
confidence: 99%
“…model of structural reflection (MSR) parents patient's satisfaction therapeutic communication & Amiegheme, 2016). But according to research (Younis, Mabrouk, & Kamal, 2015) there are 71% of health service providers accustomed to poor communication, as well as incomplete culture and information exchange. Based on research by (Agustin, Kusnanto, & Sulistiawati, 2017), that with providing training interventions interventions to nurses using MSR has a positive effect in influencing changes in empathy in the communication made by nurses to the patient's family.…”
mentioning
confidence: 99%